Finite element analysis of fluid influence on instabilities in two-phase Cam-clay plasticity model - Stankiewicz, Anna; Pamin, Jerzy (Computer Assisted Methods in Engineering and Science, 2006)
The influence of fluid phase on soil instabilities is investigated using the modified Cam-clay model within a two-phase description. Spurious mesh dependence of finite element results is prevented by a gradient enhancement of the model. The results of numerical tests for one-phase and two-phase model are compared. The influence of permeability on the stabilizing role of the fluid phase is assessed.